Temperature–Induced Hatch Failure and Nauplii Malformation in Antarctic Krill - Perry, Frances A.; Kawaguchi, So; Atkinson, Angus; Sailley, Sévrine F.; Tarling, Geraint A.; Mayor, Daniel J.; Lucas, Cathy H.; King, R.; Cooper, A. (Frontiers in Marine Science, 2020)
Antarctic krill inhabit areas of the Southern Ocean that can exceed 4.0°C, yet they preferentially inhabit regions with temperatures of -1.5 to ≤1.5°C. Successful embryonic development and hatching are key to their life cycle, but despite the rapid climatic warming seen across their main spawning areas, the effects of elevated temperatures on embryogenesis, hatching success and nauplii malformations are unknown. We incubated 24,483 krill embryos in two independent experiments to investigate the hypothesis that temperatures exceeding 1.5°C have a negative impact on hatching success and increase the numbers of malformed nauplii. Field experiments were on krill collected from near the northern, warm limit of their range and embryos incubated soon after capture, while laboratory experiments were on embryos from krill acclimated to laboratory conditions. The hatching success of embryo batches varied enormously, from 0-98% (mean 27%). Both field and laboratory experiments showed that hatching success decreased markedly above 3.0°C. Our field experiments also showed an approximate doubling of the percentage of malformed nauplii at elevated temperatures, reaching 50% at 5.0°C. At 3.0°C or below however, temperature was not the main factor driving the large variation in embryo hatching success. Our observations of highly variable and often low success of hatching to healthy nauplii suggest that indices of reproductive potential of female krill relate poorly to the subsequent production of viable krill larvae, and may help to explain spatial discrepancies between the distribution of the spawning stock and larval distribution.